2009
DOI: 10.1080/10862960902908491
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the History and Logic of Negative, Ambivalent, and Positive Responses to Literature: A Case-Study Analysis of Cultural Models

Abstract: This paper begins with the assumption that the interpretive practices people acquire in social worlds often transfer to their stances toward and interpretations of worlds encountered in literature (Beach, Thein, & Parks, 2007). The goal of this paper is to identify the history and logic behind one student's negative, ambivalent, and positive responses to classroom texts. This paper joins socio-cultural theories of response to literature (Galda & Beach, 2001) with theories of identity (Holland, Lachicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 40 publications
(44 reference statements)
0
28
0
Order By: Relevance
“…Yet somehow that engagement is persistently difficult to translate into engagement with school-sanctioned texts. Thein's (2009) work points to similarities between the research that she has conducted with girls and their reading practices both inside and outside of schools. Specifically, in one study Thein found that Molly, an 11th-grade student, although a good student, was rarely engaged in school literature and was often disengaged because she read for different purposes outside of class than she did in school.…”
Section: Limitationsmentioning
confidence: 94%
“…Yet somehow that engagement is persistently difficult to translate into engagement with school-sanctioned texts. Thein's (2009) work points to similarities between the research that she has conducted with girls and their reading practices both inside and outside of schools. Specifically, in one study Thein found that Molly, an 11th-grade student, although a good student, was rarely engaged in school literature and was often disengaged because she read for different purposes outside of class than she did in school.…”
Section: Limitationsmentioning
confidence: 94%
“…Amanda Thein (2009) also sought to understand the connection between students' out-of-school literacies and classroom learning. In a case study, Thein (2009) documented how a White high school student, Molly, responded to school-sanctioned texts through the lens of her out-of-school literacies; describing how Molly's out-ofschool reading centered around "'confessional' (Greer, 2004) popular fiction and nonfiction that divulges the true stories (or seemingly true stories) of people struggling with unpredictable and uncontrollable difficulties in their lives" (p. 294).…”
Section: Similarly Schools Out!: Bridging Out-of-school Literacies Wmentioning
confidence: 99%
“…Amanda Thein (2009) also sought to understand the connection between students' out-of-school literacies and classroom learning. In a case study, Thein (2009) documented how a White high school student, Molly, responded to school-sanctioned texts through the lens of her out-of-school literacies; describing how Molly's out-ofschool reading centered around "'confessional' (Greer, 2004) popular fiction and nonfiction that divulges the true stories (or seemingly true stories) of people struggling with unpredictable and uncontrollable difficulties in their lives" (p. 294). Since what Molly chose to read outside of school aligned with Molly's cultural models, defined as "more or less conscious conceptions of themselves as actors in socially and culturally constructed worlds" (Holland, Lachicotte, Skinner, & Cain, 1998, p. 40), Molly relied upon her cultural models to judge and assess the worth of books assigned to her in class.…”
Section: Similarly Schools Out!: Bridging Out-of-school Literacies Wmentioning
confidence: 99%
See 2 more Smart Citations